Lightning Protection and Grounding Technology for Photoelectric Buildings - WU Xiaoyun; LI Jianquan; ZHAI Wenjie; CHENG Yuxu (Kongzhi Yu Xinxi Jishu)
It presents the harm of lightning to photoelectric building, particularly introduces the probability calculation methods of direct lightning subjected by photoelectric buildings and the classification principles of lightning protection level. According to the lightning protection requirements of direct lightning, lightning induction and grounding, the design principles of photoelectric building are put forward. It can be a reference of the design and construction of lightning protection and grounding for photoelectric buildings.